Pemetaan Potensi Karbon Biru pada Kawasan Mangrove di Kabupaten Kayong Utara - Raynaldo, Adityo; Saputra, Robin; Zibar, Zan (Universitas Diponegoro, 2024)
Distribution and extent of existing mangroves, conditions, and potential for blue carbon are needed to encourage the economy of coastal communities as coastal ecosystem services. Kayong Utara Regency as one of the regencies in the coastal area of West Kalimantan has the potential for mangroves to be utilized by coastal communities but there has been no ecological study of the potential for blue carbon contained therein. This study aims to map the distribution of mangroves and their conditions and to map the spatial distribution of mangrove carbon stocks in the Kayong Utara Regency. The mapping method for the distribution of existing mangroves is carried out using the visual interpretation method by making a certain false-color RGB composite, the distribution of mangroves is identified using nine key elements of image interpretation. Mangrove conditions were analyzed through mangrove cover using the hemispherical photography method. Mapping of carbon stocks was carried out using a linear regression model formulation of several vegetation index variables and carbon stock values from making observation plots, then analyzed spatially. The research results show that the mangrove area in North Kayong Regency is 20,543.40 ha, spread throughout the district. Mangrove conditions consist of the categories rare 3.92%, moderate 53.07%, and dense 43.01%. Tree density (DBH ≥ 10 cm) from 56 survey points ranged from 100 – 2800 individual ha-1 with AGC values ranging from 4.21 – 1375.74 Mg ha-1. The dominant mangrove species found included Avicennia alba, A. lanata, A. marina, Bruguiera parviflora, Excoecaria agallocha, Rhizophora apiculata, R. mucronata, R. stylosa, Xylocarpus granatum. The best linear regression model in this study uses the MDI2 variable with the formulation y = 225.08x – 114.55 and the Pearson correlation value (r) = 0.377. The AGC potential value of the selected model ranges from 0 – 631.92 Mg ha-1 spread with the largest potential value found in Pulau Maya District. Data sebaran dan luasan mangrove eksisting, kondisi dan potensi karbon biru diperlukan untuk mendorong peningkatan ekonomi masyarakat pesisir sebagai jasa ekosistem pesisir yang masih terbatas saat ini. Kabupaten Kayong Utara sebagai salah satu Kabupaten di wilayah pesisir Kalimantan Barat memiliki potensi mangrove yang dimanfaatkan oleh masyarakat pesisir namun belum ada kajian ekologis tentang potensi karbon biru yang terdapat didalamnya. Penelitian ini bertujuan untuk memetakan sebaran mangrove dan kondisjnya serta memetakan distribusi spasial stok karbon mangrove di Kabupaten Kayong Utara. Metode pemetaan sebaran mangrove eksisting dilakukan dengan menggunakan metode interpetasi visual dengan membuat komposit false-color RGB tertentu, sebaran mangrove diidentifikasi dengan menggunakan sembilan unsur kunci interpetasi citra. Kondisi mangrove dianalisis melalui tutupan mangrove dengan metode hemispherical photography. Pemetaan stok karbon dilakukan dengan formulasi model regresi linear beberapa variabel indeks vegetasi dan nilai stok karbon dari pembuatan plot pengamatan, kemudian dianalisis secara spasial. Hasil penelitian menunjukkan luasan mangrove di Kabupaten Kayong Utara sebesar 20.543,40 ha, tersebar di seluruh Kecamatan. Kondisi mangrove terdiri atas kategori jarang 3,92%, sedang 53,07% dan rapat 43,01%. Kerapatan pohon (DBH ≥ 10 cm) dari 56 titik survey berkisar antara 100 – 2800 ind ha-1 dengan nilai AGC berkisar 4,21 – 1375,74 Mg ha-1. Spesies mangrove dominan yang ditemukan antara lain Avicennia alba, A. lanata, A. marina, Bruguiera parviflora, Excoecaria agallocha, Rhizophora apiculata, R. mucronata, R. stylosa, Xylocarpus granatum. Model regresi linear yang terbaik pada penelitian ini menggunakan variabel MDI2 dengan formulasi y = 225,08x – 114,55 dan nilai korelasi pearson (r) = 0,377. Nilai potensi AGC dari model yang dipilih berkisar antara 0 – 631,92 Mg ha-1 tersebar dengan nilai potensi terbesar terdapat di Kecamatan Pulau Maya.